ENGARUH KEPERCAYAAN PADA KESETIAAN PASIEN YANG DIMEDIASI OLEH KOMITMEN HUBUNGAN DALAM INDUSTRI RUMAH SAKIT - Siti Nurfadillah; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine patient loyalty. Patient loyalty is influenced by trust and relationship commitment. High trust and commitment will affect on patient loyalty behavior. The data collected by using questionnaires for the patients at PKU Muhammadiyah Surakarta Hospital in Surakarta with the cluster. The sampling technique used was the pur posive sampling of 200 respondents. This analysis used the regression analysis. The re sults of the study show that trust gives a positive effect on patient loyalty. Trust gives a positive effect on relationship commitment. Relationship commitment gives a positive effect on patient loyalty. Relationship commitment partially mediates the relationship between trust and patient loyalty.